2017
DOI: 10.1159/000464446
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Follow-Up of Trabeculectomy with 5-Fluorouracil

Abstract: Purpose: To evaluate the long-term outcome of trabeculectomy with intra- and postoperative 5-fluorouracil (5-FU) application in glaucoma. Methods: Eighty-six patients with glaucoma planned for primary trabeculectomy with 5-FU and a minimum follow-up of 3 years were retrospectively analyzed. Success rates, postsurgical 5-FU injections, needling procedures, and complications were analyzed. Results: Mean intraocular pressure (IOP) decreased from 27.2 ± 6.7 to 13.2 ± 4.2 mm Hg at 1 year and 13.8 ± 3.7 mm Hg at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 38 publications
0
9
0
2
Order By: Relevance
“…1 Despite the potential reduction of IOP following trabeculectomy with the use of antimetabolites, several visionthreatening complications may still occur, such as hypotony maculopathy, choroidal effusion, suprachoroidal hemorrhage, and bleb-related endophthalmitis. 1,2 The XEN gel implant, a hydrophilic, non-inflammatory, subconjunctival gelatin stent (XEN Gel Stent, Allergan, Dublin, USA), provides an ab interno approach to create a permanent channel from the anterior chamber to the subconjunctival space and is designed to avoid early postoperative hypotony. 3,4 The flexibility of the implant and its expansion upon hydration allow it to be tissue conforming and thus preventing the risk of extrusion and migration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Despite the potential reduction of IOP following trabeculectomy with the use of antimetabolites, several visionthreatening complications may still occur, such as hypotony maculopathy, choroidal effusion, suprachoroidal hemorrhage, and bleb-related endophthalmitis. 1,2 The XEN gel implant, a hydrophilic, non-inflammatory, subconjunctival gelatin stent (XEN Gel Stent, Allergan, Dublin, USA), provides an ab interno approach to create a permanent channel from the anterior chamber to the subconjunctival space and is designed to avoid early postoperative hypotony. 3,4 The flexibility of the implant and its expansion upon hydration allow it to be tissue conforming and thus preventing the risk of extrusion and migration.…”
Section: Introductionmentioning
confidence: 99%
“…Trabeculectomy remains the gold standard of surgical glaucoma therapy. 1 Despite the potential reduction of IOP following trabeculectomy with the use of antimetabolites, several vision-threatening complications may still occur, such as hypotony maculopathy, choroidal effusion, suprachoroidal hemorrhage, and bleb-related endophthalmitis. 1,2…”
Section: Introductionmentioning
confidence: 99%
“…International and domestic studies reported that IOP drop rate of trabeculectomy combined with anti-metabolizing drugs or releasable sutures in PACG patients was 44-70% [13]. The success rate of trabeculectomy at 6 months postoperatively was 72%-91% [14] and 54-65% at 3 years postoperatively [15][16][17], which depends on follow-up time and the criteria used to define the successful outcome. In our study, no visible filtering blebs were observed in all eyes 3 months post-operatively (Figure 3), which fully demonstrated the efficacy of internal Schlemm's canal drainage.…”
Section: Discussionmentioning
confidence: 99%
“…Для обеспечения стабильного и длительного гипотензивного эффекта после антиглаукомных операций нередко используются антиметаболические препараты (5-фторурацил, митомицин С), препятствующие пролиферации тканей в зоне вмешательства с рубцеванием искусственно созданных путей оттока внутриглазной жидкости [2][3][4][5][6]. Однако широкое применение антиметаболитов ограничено из-за риска развития в послеоперационном периоде таких осложнений, как вторичная макулопатия, кератопатия, прогрессирование катаракты, гипотония глаза [2].…”
Section: Introductionunclassified